Influencia de la inteligencia emocional en el desempeño directivo en las instituciones educativas públicas del nivel primaria de la localidad de Requena, 2020 - Angulo Rodríguez, Delio Martin (2022)
The objective of the study was to explain the influence of Emotional Intelligence on managerial performance in the perception of teachers of public educational institutions at the Primary level of the town of Requena, 2020. The study was explanatory and designed: field, transectional and bivariate. The sample consisted of 149 teachers from different primary schools in the city of Requena. The technique used to collect data was the survey and the questionnaire as an instrument; the same ones that were validated and trusted as data collection tools. The results of the study were that 63.8% of the directors of the Primary Level of the Public Educational Institutions have an excellent level of motivation and, on the other hand, 71.8% of the directors had a good performance. In the bivariate analysis, the existence of a highly significant correlation between emotional intelligence and managerial performance was verified in the perception of education teachers at the primary level of public educational institutions in the town of Requena (p-value < 0.01). Therefore, it is concluded that there is a significant influence of emotional intelligence on managerial performance from the perception of the teacher (binary logistic regression, p-value = 0.000 <0.05).